Resensi Buku: : Filsafat Pendidikan Kristen: Meletakkan Fondasi dan Filosofi Pendidikan Kristen di Tengah Tantangan Filsafat Dunia - Sandi Lau (TRANSFORMATIO: Jurnal Teologi, Pendidikan, dan Misi Integral, 2024)
The book Philosophy of Christian Education is a book written by Khoe Yao Tung to help Christian educators understand the basis or foundations of Christian education. This book is one of the books by Khoe Yao Tung which is quite well known and is often used as a reference by Christian educators because this book was written through his experience of approximately 20 years in the world of education. Khoe Yao Tung is an educator, writer and lecturer. He has written more than two dozen books covering the fields of Physics, Mathematics, Computers, Management and Education. Apart from that, Khoe Yao Tung has also served in the MPK organization (2007-2012), DPP Indonesian Lecturers Association (2017-2022), served as head of IPEKA Christian School Curriculum Development and founded The Indonesian Chapter of Christian Education.